Pengembangan Hypothetical Learning Trajectory Berbasis Realistics Mathematics Education Geometri Transformasi pada Topik Rotasi - Ismail, Rafki Nasuha; Fauzan, Ahmad; Arnawa, Made; Armiati, Armiati (Lattice Journal : Journal of Mathematics Education and Applied, 2021)
The purpose of this research is to produce a Hypothetical Learning Trajectory for geometric transformation material on the topic of rotation using the context of batik motifs and the Ferris wheel game. The research method used is design research. The learning approach used is Realistic Mathematics Education Indonesia (RME). Hypothetical Learning Trajectory (HLT) was developed from learning activities using the context of batik motifs and the Ferris wheel game. The research subjects were three students of class IX SMPN 7 Bukittinggi. Theoretical development was carried out through designing learning activities with HLT design at the preliminary stage, carrying out one to one activities in teaching experiments and retrospective analysis. Data was collected by observation, interviews, and documentation. After the observations were made, the results of the LKPD work were collected which were given to students, interviewed students. The results obtained from the interview process, students can use the HLT design that was developed because it has a systematic guide sequence to teach the topic of geometric transformation about rotation in the one to one implementation. what is predicted and what is anticipated. So the results of the HLT design for geometric transformation materials on the topic of rotation using the context of batik motifs and the Ferris wheel game are obtained.Tujuan penelitian menghasilkan Hypothetical Learning Trajectory materi transformasi geometri pada topik rotasi menggunakan konteks motif batik dan permainan bianglala. Metode penelitian yang digunakan adalah design research Pendekatan pembelajaran yang digunakan adalah Realisticcs Mathematics Education Indonesia (RME). Hypothetical Learning Trajectory (HLT) dikembangkan dari aktivitas pembelajaran menggunakan konteks motif batik dan permainan bianglala. Subjek penelitian adalah tiga peserta didik kelas IX SMPN 7 Bukittinggi, Pengembangan secara teoritis dilaksanakan melalui perancangan aktivitas pembelajaran dengan desain HLT pada tahap preliminary, melaksanakan kegiatan one to one pada teaching experiment dan restrospective analysis. Pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Setelah observasi dilakukan maka dikumpulkan hasil pengerjaan LKPD yang diberikan pada peserta didik, mewawancarai peserta didik. Hasil penelitian diperoleh proses wawancara, peserta didik dapat menggunakan desain HLT yang dikembangkan karena memiliki urutan panduan yang sistematis untuk mengajarkan topik transformasi geometri tentang Rotasi padaÂ  pelaksanaan one to one menunjukkan bahwa penggunaan konteks motif batik dan permainan bianglala pada desain HLT transformasi geometri tentang Rotasi sesuai antara apa yang diprediksi dan antipasi yang dilakukan. JadiÂ  diperoleh hasil rancangan HLT materi transformasi geometri pada topik rotasi menggunakan konteks motif batik dan permainan bianglala.